Towards an atomic Sagnac interferometer with full dynamical control of atoms in ring waveguides - Gentile, Fabio (2019)
The advances towards a fully guided matter-wave rotation sensor are illustrated in this document. As in optical gyroscopes, the presented interferometer is based on the Sagnac effect, i.e. the phase difference accumulated between two waves counter propagating in a closed loop that is rotating with respect to an inertial frame of reference. Besides being a recent field of study, atomic Sagnac interferometry already presents results comparable to commercial devices based on the well established optical technology. Differently from other atom based devices, in the studied scheme atomic clouds are steered around a ring trap in a controlled fashion, instead of using free propagating atomic beams. This thesis reports on the current status of the experimental apparatus and on the experimental feasibility of the interferometric protocol. Moreover, a new technique to produce closed loop lattices is presented. This consists in dressing a ring shaped magnetic quadupole with multi-pole fields oscillating in the radio frequency regime. The state dependent potential landscape produced is dynamically controllable and can be used to improve the current interferometric design. Moreover, it opens for more fundamental applications in lattice physics and, in general, quantum simulators.